2023
DOI: 10.3390/nu15051115
|View full text |Cite
|
Sign up to set email alerts
|

A Sarcopenia Index Derived from Malnutrition Parameters in Elderly Haemodialysis Patients

Abstract: (1) Background: Persons with chronic kidney disease may have sarcopenia characterized by the loss of muscle mass and loss of muscle strength. However, EWGSOP2 criteria to diagnose sarcopenia are technically challenging, especially in elderly persons on hemodialysis. Sarcopenia may be associated with malnutrition. We aimed at defining a sarcopenia index derived from malnutrition parameters for use in elderly haemodialysis patients. (2) Methods: A retrospective study of 60 patients aged 75 to 95 years treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…A clinical study found that the elderly hemodialysis sarcopenia index (EHSI) can identify sarcopenia diagnosed by the European Working Group on Sarcopenia in Older People (EWGSOP) second meeting using easily accessible anthropometric and nutritional parameters. A combination of gender, age, serum albumin, phosphate, and cholesterol can effectively predict the severity of sarcopenia [179]. The current nutritional therapy for uremic sarcopenia includes oral supplements, parenteral nutrition, enteral nutrition, high protein and fiber diet, and gastrectomy [180].…”
Section: Other Possible Therapeutic Strategiesmentioning
confidence: 99%
“…A clinical study found that the elderly hemodialysis sarcopenia index (EHSI) can identify sarcopenia diagnosed by the European Working Group on Sarcopenia in Older People (EWGSOP) second meeting using easily accessible anthropometric and nutritional parameters. A combination of gender, age, serum albumin, phosphate, and cholesterol can effectively predict the severity of sarcopenia [179]. The current nutritional therapy for uremic sarcopenia includes oral supplements, parenteral nutrition, enteral nutrition, high protein and fiber diet, and gastrectomy [180].…”
Section: Other Possible Therapeutic Strategiesmentioning
confidence: 99%